Vertical Raindrop Size Distribution in Central Spain: A Case Study. (30th August 2015) - Fraile, Roberto; Castro, Amaya; González-Colino, Miguel; Alonso-Blanco, Elisabeth; Fernández-Raga, María; Palencia, Covadonga; Calvo, Ana I.
Abstract : A precipitation event that took place on 12 October 2008 in Madrid, Spain, is analyzed in detail. Three different devices were used to characterize the precipitation: a disdrometer, a rain gauge, and a Micro Rain Radar (MRR). These instruments determine precipitation intensity indirectly, based on measuring different parameters in different sampling points in the atmosphere. A comparative study was carried out based on the data provided by each of these devices, revealing that the disdrometer and the rain gauge measure similar precipitation intensity values, whereas the MRR measures different rain fall volumes. The distributions of drop sizes show that the mean diameter of the particles varied considerably depending on the altitude considered. The level at which saturation occurs in the atmosphere is decisive in the distribution of drop sizes between 2, 700 m and 3, 000 m. As time passes, the maximum precipitation intensities are registered at a lower height and are less intense. The maximum precipitation intensities occurred at altitudes above 1, 000 m, while the maximum fall speeds are typically found at altitudes below 700 m.